Estudo de filmes híbridos de celulose e polímeros sintéticos para imobilização de nanopartículas de prata - Barroso, Bruno Lupi [UNIFESP] (2018)
Microcrystalline cellulose and hydropropylmethylcellulose (HPMC) films, added with two synthetic polymers, polyvinylalcohol (PVA) and polyvinylpyrrolidone (PVP), were produced on the present study. The aim of PVA and PVP addition was to manufacture more transparent cellulose films with better mechanical properties. Microcrystalline cellulose films containing PVA and PVP were prepared by two methods. In method A, all polymers were solubilized in an ionic liquid, 1-butyl-3- methylimidazolium (BMImCl), while in method B the synthetic polymers were dissolved in dimethyl sulfoxide (DMSO) and then mixed in the dissolved cellulose, using BMImCl as solvent. HPMC films containing PVA and PVP were prepared by mixing the aqueous solutions of all the polymers and subsequent water removal. Cellulose films containing PVA or PVP, prepared by methods A and B, were obtained by the addition of water in the cellulose solution containing the synthetic polymers. Although they are soluble in water, both PVA and PVP remain in the cellulose film due to the interactions, via hydrogen bonds, that they establish with cellulose. The PVA addition generates more transparent films than the cellulose one. The PVP addition generates more transparent films only when DMSO is used in the process. In general, the cellulose films containing PVA and PVP are amorphous and exhibit similar thermal stability than the cellulose film. The mechanical properties of films containing cellulose and PVA/PVP have not been markedly improved over the cellulose film. HPMC films are colorless and their transparency increase as the concentration of PVA or PVP increases. The films are amorphous and there is good miscibility between the biopolymer and the synthetic polymers within the different proportions tested. HPMC establishes hydrogen bonds with PVA and PVP. The thermal stability of the films is high. The elongation capacity of the films also increases as the concentration of synthetic polymer increases. Aiming to use HPMC films with greater transparency and better mechanical properties as curatives for second degree burns, 2.5% by mass of silver nanoparticles were added to these films. They exhibited microbicidal activity against S. aureus and E. coli.